Quilted cellphilm method: A participatory visual health research method for working with marginalised and stigmatised communities. Issue 7 (3rd July 2022) - MacEntee, Katie; Kendrick, Caterina; Flicker, Sarah
ABSTRACT: The use of participatory visual methods and integration of cellphone technology is expanding in global public health research. Cellphilm method capitalises on these trends by inviting participants to use mobile devices to create short videos about health topics. This paper presents the quilted cellphilm method, which supports the participation of stigmatised populations to engage in research. We present the method with reference to the Celling Sex project, which worked with young women who have transactional sex experience. Four key steps in our unique model are discussed: (a) individual cellphilm-making; (b) participatory analysis; (c) creating a composite video; (d) publicly screening the work. We consider how working individually with participants in the cellphilm-making process built trust. We unpack how offering participants opportunities to engage in either group or one-on-one activities promoted participation in collaborative analysis. We outline how creating a composite video of the cellphilms and organising screenings facilitated knowledge translation and exchange. Overall, the quilted cellphilm method created a supportive community for vulnerable participants to generate products that challenged social stigma. Increased reliance on mobile media, especially during the COVID-19 pandemic, makes the quilted cellphilm method an opportune, exciting and accessible approach for participatory public health research.